Assessment of growth status in children and adolescents with type 1 diabetes mellitus in Baghdad: a case-control study - Farah Tareq Salih; Wasnaa Hadi Abdullah; Basma Adel Ibrahim; Najla Ibrahim Ayoub (Journal of the Pakistan Medical Association, 2024)
Objective: To assess growth parameters in adolescents and children with type 1 diabetes mellitus, and the factors influencing their growth. Method: The case-control study was conducted from February to December 2020 at the Endocrine Outpatient Clinic of the Central Child Teaching Hospital of Paediatrics, Baghdad, Iraq, and comprised patients aged 2-16 years who had type 1 diabetes for at least a year. The patients formed group A, while healthy control matched for age and gender from different schools and kindergartens formed group B. Weight, height and body mass index of all the subjects in both groups were measured and worked out, and the values were compared. Data was analysed using SPSS 25. Results: Of the 192 subjects, 96(50%) were in each of the 2 groups; 50(52.1%) girls and 46(47.9%) boys in group A, and 58(60.4%) girls and 38(39.6%) boys in group B. The overall mean age was 9.66±3.26 years. Group A children had significantly lower mean height, weight and body mass index Z scores compared to group B (p=0.001). The height Z score of group A children was significantly inversely associated with age, duration of disease, and glycated haemoglobin level (p=0.001), while the weight Z score was significantly inversely correlated with age and glycated haemoglobin (p=0.001). The body mass index Z score of group A was significantly inversely associated with age and glycated haemoglobin level (p<0.05). Conclusion: Children with type 1 diabetes mellitus had significantly lower mean height, weight and body mass index Z scores compared to their counterparts in the control group. Pubertal age group, poor glycaemic control, longer disease duration, and using conventional insulin regimen were the factors affecting growth parameters. Key Words: Diabetes, Glycated Hemoglobin, Glycemic, Ambulatory Care, Insulins